PHYTOCHEMICAL CONTENT TEST OF WILD TALAS BENENG LEAF (Xanthosoma undipes K.KOCH) AT GUNUNG KARANG, BANTEN - Nuniek Hermita; Andi Apriany Fatmawaty; Dewi Hastuti (Agros Journal of Agriculture Science, 2019)
Talas beneng (Xanthasoma undipes K. koch) is a local plant typical of Mount Karang, Banten Province, which belongs to the family Araceae and is perennial herbaceous. At present there has been a lot of development of products made from talas beneng into local food sources. However, there are other parts of the talas beneng plant that have not been utilized, namely the talas beneng leaves. This study aims to determine the chemical content of the talas beneng leaves as raw materials for vegetable pesticides towards environmentally friendly agriculture. The study was conducted from June to September 2018. Samples of talas beneng leaves were taken in the Gunung Karang area, Pandeglang Regency. Then do a laboratory test. This study uses a quantitative descriptive method approach. The parameters observed included phytochemical analysis in the form of alkaloids, flavonoids, saponins, tannins, and oxalic acid. The test results showed negative found in flavonoids, alkaloids, and saponins. While the test results showed positive found in tannin content with the results of 2337.90 mg / kg and oxalic acid with the results of 7430.52 mg per kg